Sustainability Reporting And Stock Return In LQ45 Indexed Companies - Ni Luh Tania Noviantini; I Ketut Jati (SEAN Institute, 2024)
The purpose of this study is to determine how the effect of sustainability reporting on stock returns of LQ45 companies in 2021-2022, using a purposive sampling approach so that a total sample of 73 companies is obtained. Data was collected by visiting the IDX website with a non-participant observation approach. This study uses multiple linear regression analysis as a data analysis technique with the help of the IBM SPSS program. The results of the analysis show that sustainability reporting has no effect on stock returns, profitability projected by return on equity has a negative effect on stock returns, solvency projected by debt to equity ratio has no significant effect on stock returns, and company size projected by ln total assets has a significant effect on stock returns.